The role of connexin-43 in modeling arrhythmogenic diseases with induced pluripotent stem cell-derived cardiomyocytes - Ke, Xijian; Baillie, Jonathan S.; Lemma, Enrico D.; Bastmeyer, Martin; Hecker, Markus; Ullrich, Nina D. (Journal of molecular and cellular cardiology, 2025)
A common pathophysiological characteristic of arrhythmic diseases is the disruption of electrical signal transmission across the heart causing life-threatening rhythm disorders. These conditions are associated with decreased expression of connexin-43 (Cx43) at intercalated discs and its translocation to the lateral membranes, however, the underlying mechanisms remain unclear. Induced pluripotent stem cell-derived cardiomyocytes (iPSC-CM) offer a model for studying these pathophysiological processes. Here, we tested the hypothesis that chronic stress, usually preceding arrhythmic developments, modulates Cx43 expression. iPSC-CM were electrically stimulated at a normal rate and by tachypacing, and their electrical and Ca2+ signaling properties were analyzed. Our data revealed that tachypacing significantly reduced Cx43 expression by a micro-RNA miR-1-dependent mechanism. Anti-miR-1 treatment restored Cx43 expression in conditions of stress, enhanced Na+ currents, improved Ca2+ propagation and synchronized electrical activity. These findings suggest miR-1 as a potential pharmacological target for mitigating arrhythmogenic remodeling and restoring robust electrical signal transmission in cardiomyocytes.